2020
DOI: 10.1002/fsn3.1636
|View full text |Cite
|
Sign up to set email alerts
|

Health risks from consumption of medicinal plant dietary supplements

Abstract: The aim of this study was to determine the heavy metal contents of dietary supplements manufactured from medicinal plants and assess the potential daily burden on their consumers. The study consisted of 41 dietary supplements produced from terrestrial plants or microalgae. The analysis of cadmium, lead, and mercury content was performed using analytical methods. The content of Cd and Pb was determined by flame atomic absorption spectrometry (FAAS). The mercury content was determined using atomic absorption spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…In addition, in a study carried out in Poland, the content of Cd, Pb, and mercury was analyzed in 41 dietary supplements of herbal origin. It was found that 68% of the products were contaminated with Cd and Pb, as reported in our study, although only a single product exceeded the permissible daily limits of Pb according to Poland s regulations [53].…”
Section: Discussionsupporting
confidence: 81%
“…In addition, in a study carried out in Poland, the content of Cd, Pb, and mercury was analyzed in 41 dietary supplements of herbal origin. It was found that 68% of the products were contaminated with Cd and Pb, as reported in our study, although only a single product exceeded the permissible daily limits of Pb according to Poland s regulations [53].…”
Section: Discussionsupporting
confidence: 81%
“…This parameter was obtained by summing the THQ values for each metal, which are calculated for an average person of 70 kg and 70 years of age. TTHQ values less than or equal to 1 indicate that exposure does not cause side effects, and values greater than 1 do not necessarily suggest a high probability of producing some side effects on consumer health [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The exploration of the functional attributes of several edible fruits has emerged as suitable food materials for the development of promising dietary supplements. A desire for such developments is surging and the food supplement market is flourishing with overwhelming and unprecedented dynamics (Ćwieląg‐Drabek et al., 2020). The choice of dietary supplements has increased as an easy way to enrich the daily diet.…”
Section: Introductionmentioning
confidence: 99%